Benzene Exposure Analysis through S-Phenylmercapturic Acid in Urine at Platelet Levels in Footwear Workers in Sukajaya Village, Bogor Regency - Norjannah, Siti; Wulandari, Ririn Arminsih; Asyary, Al (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Benzene is a toxic and carcinogenic compound whose presence in glue is endangering the health of workers in footwear workshops. One of its negative effects is its disruption of the bone marrow, which is where red blood cells, white blood cells, and platelets are produced. AIM: The purpose of this study was to analyze the relationship of benzene exposure with platelet levels in workers through examination of S-phenylmercapturic acid (S-PMA) concentrations in urine. METHODS: The design of the study was cross sectional, with 73 workers used as samples. The concentration of S-PMA was measured using Liquid chromatography-Mass Spectrometry/Mass Spectrometry and platelet counts using an automated hematology analyzer. Direct interview was used to retrieve workers’ individual characteristics. RESULTS: The results showed an odds ratio (OR) value of 2.28 for correlation between S-PMA concentration and platelet levels. The results also showed an OR value of 1.58 for correlation between non-routine exercise habits and platelet levels and an OR value of 1.78 for correlation between alcohol consumption and platelet levels. Multivariable logistic regression test results showed an OR of 2.59 for workers with S-PMA concentration (>0.67 μg/g creatinine) on platelet counts after controlling for the variables of age and alcohol consumption. CONCLUSION: The study’s main recommendation is that information about the dangers of benzene in glue to health and how to avoid it should be disseminated to prevent benzene exposure.